2013
DOI: 10.1158/1055-9965.epi-13-0401
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Changes in IGF-I and IGFBP-3, and Mammographic Density among Postmenopausal Women

Abstract: A relation between the breast cancer risk factors, insulin-like growth factor-I (IGF-I) and mammographic density, is biologically plausible, but results from cross-sectional epidemiologic studies have been mixed. Our objective was to examine the relation in a longitudinal manner, that is, between the change in circulating IGF-I concentrations and the change in mammographic measures over one year. Data from an exercise intervention trial conducted in 302 postmenopausal women ages 50 to 74 years were used. Blood… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…IGFBP5 and 2q35 have both been consistently implicated in cancer, though little was known about the nature of their interaction. Molecular studies of IGFBP5 have revealed its essential role in normal mammary epithelial development (7,8,16,17), contributing to the documented involvement of the IGF signalling axis in mammary density as a risk factor for breast cancer (18)(19)(20). A recent contemporaneous study describes a neighbouring 2q35 breast cancer-associated variant nearby the locus we describe.…”
Section: Discussionmentioning
confidence: 78%
“…IGFBP5 and 2q35 have both been consistently implicated in cancer, though little was known about the nature of their interaction. Molecular studies of IGFBP5 have revealed its essential role in normal mammary epithelial development (7,8,16,17), contributing to the documented involvement of the IGF signalling axis in mammary density as a risk factor for breast cancer (18)(19)(20). A recent contemporaneous study describes a neighbouring 2q35 breast cancer-associated variant nearby the locus we describe.…”
Section: Discussionmentioning
confidence: 78%
“…Several mechanisms including metabolic and endocrine changes have been linked to dense breast tissue including cycling estrogen, elevated glucose and insulin resistance, and insulin-like growth factor 1 (IGF-1). (1719) Interestingly, reduced adiposity following metabolic surgery may be the link between these two groups of phenomena. Not surprisingly, estrogens and inflammatory cytokines produced by adipose tissue have been proposed as a mechanism whereby obesity may be associated with postmenopausal breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…There have been no published studies reporting the impact of WLS on breast density and whether both components that comprise density, i.e., the fibroglandular tissue and the adipose tissue, are affected. WLS is likely to change both these components that make up density, due to changes in growth factors and hormones such as insulin-like growth factor-1 (IGF-1), and estrogen levels after surgery [ 25 27 ]. With improvements in metabolic regulation after WLS, changes in the fibroglandular compartment of the breast may also significantly contribute to the reduction in breast cancer risk.…”
Section: Introductionmentioning
confidence: 99%